2007
DOI: 10.1116/1.2801974
|View full text |Cite
|
Sign up to set email alerts
|

Selective immobilization of biomolecules onto an activated polymeric adlayer

Abstract: The authors report a facile method for the selective immobilization of biomolecules onto a gold surface that was preactivated by a polymeric adlayer. The polymeric adlayer was designed to perform triple functions: high resistance to nonspecific protein adsorption, efficient surface anchoring, and subsequent covalent attachment of biomolecules. For this purpose, a random copolymer, poly(PEGMA-r-NAS), was synthesized by radical polymerization of poly(ethylene glycol) methyl ether methacrylate (PEGMA) and N-acryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Reaction of NHS ester with azido-PEG 3 -amine results in disappearance of the peaks assigned to the NHS carbonyl group and carbonate, and the appearance of peaks assigned to the amide group stretching at 1698 cm −1 , azide stretching at 2094 cm −1 , and CH 2 scissoring at 1558 cm −1 (spectrum C). Similar spectra have been reported for amine functionalized DSC surfaces [16].…”
Section: Characterization Of Modified Membranessupporting
confidence: 85%
“…Reaction of NHS ester with azido-PEG 3 -amine results in disappearance of the peaks assigned to the NHS carbonyl group and carbonate, and the appearance of peaks assigned to the amide group stretching at 1698 cm −1 , azide stretching at 2094 cm −1 , and CH 2 scissoring at 1558 cm −1 (spectrum C). Similar spectra have been reported for amine functionalized DSC surfaces [16].…”
Section: Characterization Of Modified Membranessupporting
confidence: 85%
“…In another publication the same group used a polymer containing PEG as well as NHS functionality as a reactive coating on amino-SAMs on Au. 145 Part of the NHS groups served as covalent links to the amine surface. Residual NHS groups were then used to pattern amino-biotin by mCP which could afterwards be complexed by streptavidin.…”
Section: Non-covalent Immobilization On Polymer Substratesmentioning
confidence: 99%
“…The selective conjugation with streptavidin on the biotinylated copolymeric films and the relevant S/N ratio were evaluated by measuring the adsorbed protein using ellipsometry and SPR. The optimal S/N ratio is 339.8, which is 69.3 times higher than the previously reported result ( S/N = 4.9) from an activation‐free method . The developed method in this study is also superior to the surface modification method with an activation step that resulted in 223.6 as S/N ratio .…”
Section: Introductionmentioning
confidence: 44%
“…For example, a reactive thin polymer film was fabricated as a platform for the immobilization of biomolecules on various substrates such as silicon wafer, glass, and gold substrates . We synthesized the copolymers with non‐biofouling and bioactive groups and grafted the copolymers onto silicon oxides and gold substrates by the formation of polymeric self‐assembled monolayers (SAMs) and amide coupling, respectively. While removing the activation step, it was found that the previously reported polymeric films had lower S/N ratios (defined as the ratio of specific binding capacity to non‐specific one) than DSC‐activated poly(OEGMA) films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation